The Predictive Role of Information Literacy in English Reading Comprehension among Midwifery Students - Donal, Andri; Dewanti, Ratna; Lustyantie, Ninuk (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
In health education contexts where English is the primary medium for academic and professional communication, the ability to comprehend and critically engage with English texts is essential. For midwifery students, who frequently encounter clinical guidelines, research literature, and patient education materials in English, this competency is closely tied to their academic and professional success. This study investigates the relationship between information literacy and English reading comprehension, with the aim of determining the extent to which information literacy skills contribute to students' reading performance. A quantitative correlational design was employed, involving 120 midwifery students enrolled in an English for Specific Purposes (ESP) course. Data were analyzed using Pearson correlation and simple linear regression. The results revealed a strong, positive correlation between information literacy and reading comprehension (r = 0.736, p < .001). Furthermore, regression analysis indicated that information literacy significantly predicted reading comprehension scores, accounting for approximately 53.8% of the variance (Adjusted R² = 0.538). The study emphasizes the importance of integrating information literacy into ESP curricula for midwifery and health sciences, with the goal of enhancing students' reading comprehension and preparing them for evidence-based practice in their future clinical roles.